Use of spatial pattern analysis to assess forest cover changes in the Mediterranean region of Turkey - Bozali, Nuri; Sivrikaya, Fatih; Akay, Abdullah Emin (Springer Japan Kk, 2015)
Assessment and monitoring of changes in land use are among the most important means of understanding of forest ecosystem dynamics. The main objective of this study was to investigate the spatio-temporal variability of forest cover changes by use of spatial pattern analysis. The study was performed in BaAYkonuAY Forest Enterprise in the Mediterranean city of KahramanmaraAY in Turkey. The spatio-temporal variability of forest structures from 1992 to 2012 was analyzed by use of the Geographical Information Systems tool ArcGIS 10.0 and the spatial statistical package FRAGSTATS. The results indicated that forest areas increased from 11,446 to 11,827 ha, which is approximately 2 % of the study area. There was also a substantial increase (9.7 %) in productive forests, whereas degraded forests decreased by 7.8 %. Silvicultural treatment, rehabilitation, and conversion of coppice forests to high forests were the main forces driving forest cover changes in the study area. According to FRAGSTATS results, the total number of patches increased from 554 to 1610 between 1992 and 2012. As a result, the forest ecosystem in the study area became highly fragmented over the study period, because of the increase in the number of patches and the decrease in mean patch size; this negatively affected maintenance of biodiversity in the region.
Sivrikaya, Fatih/0000-0003-0860-6747; Akay, Abdullah Emin/0000-0001-6558-9029
Keywords: Forest cover changes; GIS; Land use changes; Spatial analysis